THE COMPLEXITY OF PUMPING WATER TO THE BOTTOM OF OIL WELLS (Web of Technology: Multidimensional Research Journal, 2025)
The reduced pressure spreads along the perforation channels, and after a certain distance from the well, the influence of the perforation channels on the pressure distribution becomes negligible, and the flow takes a flat radial form in the direction of the well axis. We call the formation zone around the well up to this limit the active zone of the formation. Here, the flow has a very complex, localized structure near the perforation channels, the greatest pressure gradient and fluid flow velocity.